Efficacy of behavioural parent training program in reducing parental stress among Iranian parents of children with ADHD - Zadeh, Majid Darvishi; Baba, Maznah; Mokhtar, Halimatun Halaliah; Wan Jaafar, Wan Marzuki; Momtaz, Yadollah Abolfathi (Marsland Press, 2011)
The present quasi-experimental study was performed to evaluate the efficacy of Behavioural Parent Training Program (BPTP) in reducing parental stress. The sample for this study consists of 60 parents of children with ADHD was randomly assigned to experimental and control groups. The experimental group received the Barkley’s parent training program. All participants completed the Parental Stress Index /Short Form (PSI/SF) at four different time points. A Mixed Model ANOVA using the SPSS 19.0 (SPSS Inc., Chicago, IL, USA) was used in data analysis. The results from mixed model ANOVA reflected that mean changes in parental stress were significantly different between two groups. In addition, Post hoc analysis revealed a statistically significant decrease in parental stress only for the experimental group. The present study in line with some previous studies provides some preliminary evidence that supports the effectiveness of Barkley’s parent training program to reduce parental stress for Iranian parents with ADHD children. The implications of the study findings and limitations of the research method along with recommendations for future studies are discussed.